Strategi Kerja dan Pelatihan Terhadap Hasil Kerja di PT Tambira - Azlansyah Putra (Forum Kerjasama Pendidikan Tinggi, 2024)
ork and Training Strategy is an important aspect to achieve results. There are many results from Work Strategy, training and discipline if everything is carried out properly and will produce work results that are the goal. The purpose of this writing is to analyze and determine the influence of work strategy and training on work results at PTTambira District. Bandar Khalifah Serdang Bedagai Regency. The results of SPPSS 16 analysis of Work Strategy, training and discipline questionnaire data on work result s at PT Tambira, Bandar Khalifah District, Serdang Bedagai District, namely (1) partially the Work Strategy variable influences the work results of workers at PT Tambira, Bandar Khalifah District, Serdang Bedagai District, (2) partially Partially, the trai ning variable influences the work results of workers at PT Tambira, Bandar Khalifah District, Serdang Bedagai District, (3) simultaneously there is a positive and significant influence between the work strategy and training variables on the work results of workers at PT Tambira, Bandar Khalifah District, Serdang Bedagai District